Results of Screening of Apparently Healthy Senior and Geriatric Dogs. (17th October 2016) - Willems, A.; Paepe, D.; Marynissen, S.; Smets, P.; Van de Maele, I.; Picavet, P.; Duchateau, L.; Daminet, S.
Abstract : Background: There is a growing interest in health care of elderly dogs; however, scientific information about physical and laboratory examination findings in this age group is limited. Objectives: To describe systolic blood pressure (SBP), and results of physical examination and laboratory tests in senior and geriatric dogs that were judged by the owner to be healthy. Animals: Hundred client‐owned dogs. Methods: Dogs were prospectively recruited. Owners completed a questionnaire. SBP measurement, physical, orthopedic and neurologic examination, direct fundoscopy and Schirmer tear test were performed. Complete blood count, serum biochemistry, and urinalysis were evaluated. Results: Forty‐one senior and 59 geriatric dogs were included. Mean SBP was 170 ± 38 mmHg, and 53 dogs had SBP > 160 mmHg. Thirty‐nine animals were overweight. A heart murmur was detected in 22, severe calculus in 21 and 1 or more (sub)cutaneous masses in 56 dogs. Thirty‐two dogs had increased serum creatinine, 29 hypophosphatemia, 27 increased ALP, 25 increased ALT, and 23 leukopenia. Crystalluria, mostly amorphous crystals, was commonly detected (62/96). Overt proteinuria and borderline proteinuria were detected in 13 and 18 of 97 dogs, respectively. Four dogs had a positive urine bacterial culture. Frequency of orthopedic problems, frequency of (sub)cutaneous masses, and platelet count were significantly higher in geriatric compared with senior dogs. Body temperature, hematocrit, serum albumin, and serum total thyroxine concentration were significantly lower in geriatric compared with senior dogs. Conclusions and Clinical Importance: Physical and laboratory abnormalities are common in apparently healthy elderly dogs. Veterinarians play a key role in implementing health screening and improving health care for elderly pets.